2019
DOI: 10.1111/dme.13843
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and adiposity are independent risk factors for perinatal outcomes: a population based cohort study in Sweden

Abstract: Aims To evaluate the interaction effects of gestational diabetes ( GDM ) with obesity on perinatal outcomes. Methods A population‐based cohort study in Sweden excluding women without pre‐gestational diabetes with a singleton birth between 1998 and 2012. Logistic regression was performed to evaluate the potential independent associations of GDM and BMI with adverse perinatal outcomes as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 40 publications
11
44
0
3
Order By: Relevance
“…According to our knowledge, there is only one previous study available evaluating the interaction effects of GDM and obesity on perinatal outcomes. The study of Hildeń et al (2019) revealed no interaction effect between GDM and BMI for severe perinatal outcomes such as malformations, perinatal mortality, stillbirth, prematurity, low Apgar score, fetal distress or Erb’s palsy [28]; that study did not asses our primary outcomes. By contrast, we found that while overweight/obesity alone are associated with macrosomia, caesarean delivery, treatment at neonatal ward (obesity only), delivery induction and low Apgar score, GDM amplifies these risks.…”
Section: Discussionmentioning
confidence: 89%
“…According to our knowledge, there is only one previous study available evaluating the interaction effects of GDM and obesity on perinatal outcomes. The study of Hildeń et al (2019) revealed no interaction effect between GDM and BMI for severe perinatal outcomes such as malformations, perinatal mortality, stillbirth, prematurity, low Apgar score, fetal distress or Erb’s palsy [28]; that study did not asses our primary outcomes. By contrast, we found that while overweight/obesity alone are associated with macrosomia, caesarean delivery, treatment at neonatal ward (obesity only), delivery induction and low Apgar score, GDM amplifies these risks.…”
Section: Discussionmentioning
confidence: 89%
“…The diagnosis of gestational diabetes implies a high risk for mothers and unborn babies, because perinatal morbidity is increased in these cases when compared to the general population of pregnant women (4) . In addition, DM represents one of the main causes of maternal morbidity and mortality in the world; around 1.0% of pregnancies are correlated with maternal and fetal complications, according to a study carried out in several countries (5) .…”
Section: Introductionmentioning
confidence: 99%
“…The papers by Hild en et al and Hauffe et al [1,2] together add to the evidence that maternal obesity is a significant risk factor for serious adverse outcomes, independent of glycaemia, and that high birth weight, with all its attendant potential complications, is a complex phenomenon that cannot be equated simply with glycaemic control. Diabetes, maternal obesity and excessive gestational weight gain all increase birth weight, while factors such as smoking, inadequate weight gain, hypertensive disorders and placental insufficiency may all reduce birth weight.…”
mentioning
confidence: 99%
“…In a paper in this issue of the journal, Hildén et al . try to disentangle the impact of GDM (diagnosed by fairly liberal criteria) and maternal obesity on a number of serious pregnancy outcomes in the Swedish population. As expected, the women with GDM were older, more overweight and more likely to be migrants, multiparous and to have chronic hypertension.…”
mentioning
confidence: 99%